2020
DOI: 10.1002/jts.22529
|View full text |Cite
|
Sign up to set email alerts
|

Initial Validation and Measurement Invariance of the Active Inhibition Scale Among Traumatized and Grieving Youth

Abstract: The Active Inhibition Scale (AIS; Ayers, Sandler, & Twohey, 1998) is an 11-item, self-report measure of emotional suppression among children and adolescents. Previous research with the AIS has linked emotional suppression to several clinically significant outcomes, such as posttraumatic stress symptoms (PTSS) and suicide, among trauma-exposed and bereaved youth; however, there are no published evaluations of its psychometric properties. We examined the factor structure and criterion validity of the AIS in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The study found that child reports of their caregivers' avoidance and inhibition of grief discussions were related to higher levels of all three domains of maladaptive grief (i.e., separation distress, existential identity distress, and circumstances-related distress). The authors interpret the relation between inhibition/avoidance and higher levels of children's grief distress as possibly being due to caregiver avoidance increasing children's own inhibition of grief related emotion, which has previously been found to be associated with higher levels of child maladaptive grief, posttraumatic stress and depression symptoms (Dodd et al, 2020). There was also an unexpected relation between encouraging an ongoing connection with the deceased and higher levels of child maladaptive grief.…”
Section: Relations Of Domains Of Parenting To Children's Griefmentioning
confidence: 66%
“…The study found that child reports of their caregivers' avoidance and inhibition of grief discussions were related to higher levels of all three domains of maladaptive grief (i.e., separation distress, existential identity distress, and circumstances-related distress). The authors interpret the relation between inhibition/avoidance and higher levels of children's grief distress as possibly being due to caregiver avoidance increasing children's own inhibition of grief related emotion, which has previously been found to be associated with higher levels of child maladaptive grief, posttraumatic stress and depression symptoms (Dodd et al, 2020). There was also an unexpected relation between encouraging an ongoing connection with the deceased and higher levels of child maladaptive grief.…”
Section: Relations Of Domains Of Parenting To Children's Griefmentioning
confidence: 66%
“…The PCBD checklist (Kaplow et al, 2018; Layne et al, 2014), used in four included studies (Dodd et al, 2020; Hill et al, 2019; Hill, Oosterhoff, et al, 2019; Kaplow et al, 2018), is a 39-item self-report measure of grief in children to evaluate symptoms of the PCBD DSM-5 proposed diagnosis. Respondents are asked to indicate the frequency they experience each symptom (e.g., “I feel all alone since ___ died”; “I stay away from things that remind me that ___ died”; “I think about how things could have been different, so that __ wouldn’t have died”) on a 5-point Likert scale ranging from 0 ( not at all ) to 4 ( all the time ).…”
Section: Resultsmentioning
confidence: 99%
“…The Cronbach's αs were .89 at both time points. Research has shown evidence supporting the reliability and validity of this scale (Dodd et al, 2020).…”
Section: Posttest Mediatormentioning
confidence: 93%
“…Emotion suppression was measured at baseline and the 6 years follow-up using the Active Inhibition Scale (Ayers et al, 1998;Dodd et al, 2020) which was developed for the FBP project. This 10-item scale asks about respondents' conscious effort to avoid revealing emotions to another (e.g., "You've tried to hide any bad feelings that you've had").…”
Section: Posttest Mediatormentioning
confidence: 99%